Improving the Quality of Village Fund Financial Reporting During the COVID-19 Pandemic: Factors for Successful Use of the Village Financial Systemimproving the Quality of Village Fund Financial Reporting During the COVID-19 Pandemic: Factors for Successful Use of the Village Financial System - Fitriawan Syahadat, Edy; Idrus, Olivia; Safriansyah (Asosiasi Fakultas Ekonomi dan Bisnis Indonesia, 2023)
This study aims to determine the determining factors for the successful implementation of the village financial system (Siskeudes) in improving the quality of village fund financial reporting during the Covid-19 pandemic (Village Case Study in Sorong Regency). The records analysis method in this look at uses evaluation with the Partial Least square (PLS) technique. PLS is part or variant-based totally Structural Equation Modeling (SEM) version. The results confirmed that the implementation of the village financial device had a fine effect at the nice of village fund economic reviews. person involvement, top management help, training and training could not mild the connection between the implementation of the village economic device and the high-quality of village monetary reviews, even as consumer hobby and generation usage should mild the relationship and between the software of the village economic machine to the first-rate of village monetary reviews.